A drafter's guide to cabinet documents (Privy Council Office, 2013)
This guide provides guidance to public servants on supporting Ministers for their participation in Cabinet and Cabinet committee meetings. This guide addresses the development of Cabinet documents - Memoranda to Cabinet (MCs), presentations and aide-mémoires - for Cabinet consideration